Strengthening Socio-Cultural Ties of The Bali-Hindu Community Through Ngelungang Barong Sinarengan Tradition - Wirawan, I Wayan Ardhi; Widana, I Nyoman Murba; Sumertha, I Wayan; Kembarawan, I Gusti Komang; Sumada, I Ketut (Journal of Ecohumanism, 2024)
This study aims to conduct a study on strengthening the socio-cultural bonding of the Balinese-Hindu community through the ngelungang barong sinarengan conducted by the Hindu community in Sebatu Village, Gianyar Regency. The background of this study is the preservation of religious cultural traditions that contain important values in building social ties. This tradition is carried out in a series of galungan and kuningan holidays. This research is designed in an interpretive qualitative type using case studies. Data were collected through observation, interview, and documentation techniques. Data were analyzed by classification, reduction, and interpretation techniques. This study yielded three important findings. First, the barong is believed to be a symbol of Supernatural power and is believed to have a positive influence on improving the quality of life for Hindus, both individually and collectively. The barong symbol is believed to be a representation of the power of Lord Ҫiwa who can neutralize the negative forces caused by Bhuta Kala into positive energy that can be used as a means to improve the quality of life of Hindus implementing the tradition. Second, the tradition of the ngelungang barong sinarengan serves as a strengthening of belief in neutralizing Bhuta Kala, which is a metaphysical force that has the potential to create disharmony. Third, the tradition of the ngelungang barong sinarengan has a disposition to build socio-cultural bonds through social awareness to mutually melt the boundaries of differences that exist between them.